Republic of Congo : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Congo. (IMF Staff Country Reports; Country Report ;, 2020)
The economic situation remains difficult but there are some initial signs of stability, and non-oil growth could turn positive for the first time since 2015. The political environment is stable, though there is discontent with government policies due in part to the authorities' limited engagement with the private sector and civil society.